Power of communication as a factor of human resource management - Bajić Zoran; Karavidić Marija (Trendovi u Poslovanju)
Human resource management is undoubtedly a very complex scientific endeavor A particularly complex interactive debugging connection between the management of resources in an organization and development of communication, relationship manifested through the level of business and organizational culture. In this paper, we have tried to show the importance of communication for development and management of human resources in companies and other institutions, on the basis of theoretical and empirical findings. In accordance with our findings, we come to the conclusion that skillfully communicated, proper information, with a clear objective, at the right time and the right place - is often crucial for almost all high-quality business solutions and decision-making. Therefore, it is of great importance for the development and management of human resources to accelerate processes in the function of profit maximization. The old rule is, that it is not only important what is said, but how it is said. Upon that depends the final result. Entities in business are all its members, but managers are the ones who communicate the most. Therefore, successful managers must be familiar with the communication skills - the advantages and disadvantages of all types of communication, communication barriers and the manner of their elimination. One of the key roles of managers in the modeling of business relationships and relations is the communication management.